Culture and propagation of microsporidia of veterinary interest - Lallo, Maria Anete; Vidoto Da Costa, Lidiana Flora; Alvares-Saraiva, Anuska Marcelino; Dell'Armelina Rocha, Paulo Ricardo [UNESP]; Spadacci-Morena, Diva Denelle; Camargo Konno, Fabiana Toshie de; Suffredini, Ivana Barbosa (Japan Soc Vet Sci, 2016)
Microsporidia are obligate intracellular mitochrondria-lacking pathogens that rely on host cells to grow and multiply. Microsporidia, currently classified as fungi, are ubiquitous in nature and are found worldwide. They infect a large number of mammals and are recognized as opportunistic infection agents in HIV-AIDS patients. Its importance for veterinary medicine has been unveiled in recent years through the description of clinical and subclinical forms of infection in domestic and wild animals. Domestic and wild birds may be infected by the same human microsporidia, reinforcing their zoonotic potential. Microsporidiosis in fish is prevalent and causes significant economic losses for fish fanning. Some species of microsporidia have been propagated in cell cultures, which may provide conditions for the development of diagnostic techniques, understanding of pathogenesis and immune responses and for the discovery of potential therapies. Unfortunately, the cultivation of these parasites is not fully standardized in most research laboratories, especially in the veterinary field. The aim of this review is to relate the most important microsporidia of veterinary interest and demonstrate how these pathogens can be grown and propagated in cell culture for diagnostic purposes or for pathogenesis studies. Cultivation of microsporidia allowed the study of its life cycle, metabolism, pathogenesis and diagnosis, and may also serve as a repository for these pathogens for molecular, biochemical, antigenic and epidemiological studies.
Keywords: animal; cell culture; diagnosis; microsporidia; zoonosis